THE THE INFLUENCE OF PRODUCT MARKETING ON AQUA ON AQUA CONSUMER LOYALTY IN BANDUNG CITY - Fitri Nurlaela (STIA Bagasasi, 2023)
This research employs a survey and questionnaire method as data collection tools to elucidate the causal relationship between perceived quality and customer loyalty towards Aqua bottled water in West Java. The study follows a causal research design, with hypothesis testing as the main objective. The research sample consists of 47 respondents who are Aqua bottled water customers in Bandung, selected through purposive sampling with specific criteria. Quantitative statistics are used as the form of information in this study, utilizing both primary and secondary data sources. Data is collected through document analysis and questionnaires. The findings indicate a significant difference in the gender composition of Aqua customers in Bandung, with 89.4% being female and 10.6% male, suggesting the dominance of females as Aqua consumers in the city. Additionally, the majority of Aqua customers in Bandung fall within the 20-26 age range, indicating a prevalence of young customers among Aqua's clientele. Taste preferences, lifestyle, and hydration needs may influence this pattern. The study also reveals customers' perceptions of Aqua's packaging. Most customers view Aqua's packaging positively, which can benefit the company in building a strong brand image and enhancing customer loyalty. Water quality also proves to be a crucial factor in customers' decisions to choose Aqua as their bottled water brand.